Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The task is to find a sum of multiple values $\cos$ and $\sin$ to determine the value of $$\sum_{n=1}^\infty (-1)^n \frac{n}{(2n+2)!}$$

Since I had no clue how to approach this I consulted Wolfram|Alpha which returned this result:

$$\sum_{n=1}^\infty (-1)^n \frac{n}{(2n+2)!} = \frac{\sin(1)}{2} + \cos(1) - \cos(0)$$

So I wrote down the partial sums of the given series and $\sin(1)$ and $\cos(1)$:

$$ \qquad\qquad\quad\sum_{n=1}^\infty (-1)^n \frac{n}{(2n+2)!} = \quad - \frac{1}{4!} + \frac{2}{6!} - \frac{3}{8!} \cdots $$

$$ \;\;\sin(1) = \sum_{n=0}^\infty (-1)^n \frac{1^{2n+1}}{(2n+1)!} = 1 - \frac{1}{3!} + \frac{1}{5!} - \frac{1}{7!} \cdots $$

$$ \cos(1) = \sum_{n=0}^\infty (-1)^n \frac{1^{2n}}{(2n \qquad)!} = 1 - \frac{1}{2!} + \frac{1}{4!} - \frac{1}{6!} \cdots $$

Looking at the numbers I can see that Wolfram|Alpha's result is correct: $\frac{1}{2}1 - \frac{1}{2!} = 0$ and $\frac{1}{2}\frac{-1}{3!} + \frac{1}{4!} = \frac{1}{4!}$, so the $\cos(1)$-series is shifted by $1$ since there is no $1$ at the beginning of the given series, so it needs to be subtracted from $\cos(1)$: $-cos(0)=-1$. But how do I get here without Wolfram|Alpha?

share|improve this question
add comment

4 Answers

up vote 4 down vote accepted

No idea how Wolfram does it. But I guess you just start with power series and play around. \begin{equation} X=\sum_{n=1}^\infty(-1)^n\frac{n}{(2n+2)!}=-\frac{1}{4!}+\frac{2}{6!}-\frac{3}{8!}+\dots \end{equation} The annoying part is the numerators. Try doubling it so that the numerators "keep up" with the denominators. \begin{equation} 2X=-\frac{2}{4!}+\frac{4}{6!}-\frac{6}{8!}+\dots \end{equation} Now the numerators are consistently off the denominators by 2. \begin{equation*} 2X=(-\frac{4}{4!}+\frac{6}{6!}-\frac{8}{8!}+\dots)+2(\frac{1}{4!}+\frac{1}{6!}-\frac{1}{8!}+\dots) \end{equation*} That second part is pretty much $\cos(1)$. And the numerators of course cancel out in the first part. \begin{equation} 2X=(-\frac{1}{3!}+\frac{1}{5!}-\frac{1}{7!}+\dots)+2(\cos(1)-1/2) \end{equation} Now the first part is pretty much $\sin(1)$. \begin{equation} 2X=(\sin(1)-1)+2\cos(1)-1 \end{equation} \begin{equation} X=\frac{\sin(1)}{2}+\cos(1)-1 \end{equation}

Hope that didn't seem too random. My approach is to try to build the desired series out of ones I know using various manipulations like calculus, combining and rearranging.

share|improve this answer
    
Thanks. I chose this one as answer because it carried on my approach. –  mcb Jan 5 '12 at 7:49
add comment

Start with the known Maclaurin series

$$\cos x=\sum_{n=0}^\infty(-1)^n\frac{x^{2n}}{(2n)!}$$

and

$$\sin x=\sum_{n=0}^\infty(-1)^n\frac{x^{2n+1}}{(2n+1)!}\;.$$

The given series has factorials of even numbers in the denominator, so I began by shifting indices to make them $(2n)!$ to match the cosine series. After that it was mostly a matter of following my nose: at each step in the calculation below there’s really only one thing that suggests itself strongly.

$$\begin{align*} \sum_{n=1}^\infty (-1)^n \frac{n}{(2n+2)!}&=\sum_{n=2}^\infty(-1)^{n-1}\frac{n-1}{(2n)!}\\ &=\sum_{n=2}^\infty(-1)^{n-1}\frac{n}{(2n)!}-\sum_{n=2}^\infty(-1)^{n-1}\frac1{(2n)!}\\ &=\sum_{n=2}^\infty(-1)^{n-1}\frac{n}{2n(2n-1)!}+\sum_{n=2}^\infty\frac{(-1)^n}{(2n)!}\\ &=\frac12\sum_{n=2}^\infty\frac{(-1)^{n-1}}{(2n-1)!}+\sum_{n=0}^\infty\frac{(-1)^n}{(2n)!}-1+\frac12\\ &=\frac12\sum_{n=1}^\infty\frac{(-1)^n}{(2n+1)!}+\cos 1-\frac12\\ &=\frac12\left(\sum_{n=0}^\infty\frac{(-1)^n}{(2n+1)!}-1\right)+\cos 1-\frac12\\ &=\frac12\sin 1 + \cos 1 - 1\\ &=\frac12\sin 1+\cos 1-\cos 0 \end{align*}$$

share|improve this answer
    
Thank you, that helped a lot! –  mcb Jan 5 '12 at 6:31
add comment

Of course you know the series for $\cos(1)$ and $\sin(1)$, so you want to express this using those.
I prefer to start the sum at $n=0$: since the $n=0$ term is $0$, this is harmless. Note that $\frac{n}{(2n+2)!} = \frac{n}{(2n+1)!(2n+2)}$. Now $\frac{n}{2n+2} = \frac{1}{2} - \frac{1}{2n+2}$. So $$\sum_{n=0}^\infty (-1)^n \frac{n}{(2n+2)!} = \frac{1}{2} \sum_{n=0}^\infty (-1)^n \frac{1}{(2n+1)!} - \sum_{n=0}^\infty (-1)^n \frac{1}{(2n+2)!}$$ Now note that $ \sum_{n=0}^\infty (-1)^n \frac{1}{(2n+1)!} = \sin(1)$ and $$\sum_{n=0}^\infty (-1)^n \frac{1}{(2n+2)!} = \frac{1}{2!} - \frac{1}{4!} + \frac{1}{6!} - \ldots = 1 - \cos(1)$$

share|improve this answer
add comment

let $m=n+1$, so your series reduces to $$\sum_{m=2}^\infty(-1)^{m-1}\frac{m-1}{(2m)!}=-\sum_{m=2}^\infty(-1)^{m}\frac{m}{(2m)!}+\sum_{m=2}^\infty(-1)^{m} \frac{1}{(2m)!}$$ $$=-\sum_{m=2}^\infty(-1)^{m}\frac{1}{2(2m-1)!}+\sum_{m=0}^\infty(-1)^{m} \frac{1}{(2m)!}-1+\frac{1}{2!}$$

Note that $\frac{m}{(2m)!}=\frac{m}{(2m)(2m-1)!}=\frac{1}{(2)(2m-1)!}$, and also we evaluated the second series at $m=0$ and $m=1$

Replacing $m$ by $k+1$ in the first series and simplifying, we get, $$\sum_{k=1}^\infty(-1)^{k}\frac{1}{2(2k+1)!}+\sum_{m=0}^\infty(-1)^{m} \frac{1}{(2m)!}-1+\frac{1}{2!}$$ $$\sum_{k=0}^\infty(-1)^{k}\frac{1}{2(2k+1)!}-\frac{1}{2!}+\sum_{m=0}^\infty(-1)^{m} \frac{1}{(2m)!}-1+\frac{1}{2!}$$ $$\sum_{k=0}^\infty(-1)^{k}\frac{1}{2(2k+1)!}+\sum_{m=0}^\infty(-1)^{m} \frac{1}{(2m)!}-1$$ $$=\frac{\sin (1)}{2}+\cos(1)-\cos(0)$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.